Análise sazonal do parênquima hepático de (Anura: Hylidae) - Luciana Trevizan (2023)
The vertebrate liver is a gland responsible for processing and storing nutrients and is involved in the catabolism and anabolism of substances, as well as processes related to the detoxification of pollutants and other toxic agents. In anurans, the morphology of the hepatic components is different among some species. Anurans have in their liver tissue pigmented cells called melanomacrophages that accumulate varying amounts of melanin, lipofuscin and hemosiderin, in addition to glycogen, an energetic polysaccharide accumulated in the cytoplasm. This study aimed to analyze the liver structure, as well as the pigments and glycogen content in Dendropsophus minutus, belonging to the Hylidae family, collected over a year. Biometric (body mass, rostrum-cloacal length, scaled mass index and hepatosomatic index), stereometric (hepatic structural volumetric density) and histometric (area and cellular and nuclear volume of hepatocytes) data were analyzed, in addition to the glycogen and pigment contents of the liver. MMC. The results showed significant differences in biometric analyzes (mass and rostrum-cloacal length), while heterogeneity was observed for scaled mass and hepatosomatic indices. Hepatocyte density was lower in the warmer and more humid months (between November and March), in contrast to sinusoidal density, which was higher in the summer months, along with bile duct density. Hepatocellular morphometry showed greater cell and nuclear area and volume in the months of May and April (cold and dry). Histochemical analyzes showed no significant annual difference. Therefore, we can conclude that the hepatic components of Dendropsophus minutus studied here are influenced by seasonal variation over a year. Keywords: Amphibians, Biometry, Melanomacrophages, Pigmentation, Glycogen, Seasonality.